Determination of the significant anthropometry dimensions for user-friendly designs of domestic furniture and appliances – Experience from a study in Malaysia. (January 2015) - Dawal, Siti Zawiah Md; Ismail, Zubaidah; Yusuf, Khairi; Abdul-Rashid, Salwa Hanim; Md Shalahim, Nurul Shahida; Abdullah, Nur Suliani; Mohd Kamil, Nabilla Sofia
Highlights: Number of local poultry processing facilities has grown recently. Ergonomics risk factors were identified and assessed to determine symptoms of MSD. Main ergonomics risk factors found were awkward posture and repetitive motion. Most frequent complaints of MSDs are in lower back, lower legs, knees and feet. Abstract: Future design for the elderly is undoubtedly important for their survival to live independently in this challenging world. Therefore to realize the mentioned design, an anthropometric database for Malaysian elderly population need to be developed. A total of 107 participants took part in the study which involved 61 females and 46 males with ages ranging between 55 and 70 years. An earlier anthropometric database for Malaysian elderly population has been developed. Sixty body dimensions were measured in the study. It is hoped that from this study, the database can be used as a guideline in designing household facilities for the Malaysian elderly and elderly of other countries. The design of the household facilities should be influenced by sound ergonomics dimensions in order to create a safe and healthy environment for the elderly.